Uma análise da concorrência no setor brasileiro de celulose - Videira, Raphael Almeida (2005)
This paper studies the brazilian pulp industry and tries to answer two main questions. The first is about the definition of geographic relevant market. The second one intends to verify the existance of market power in this industry. The product relevant market, bleached eucalyptus pulp, was defined by qualitative aspects. The first question used a methodology proposed by Forni (2004), who used unit root tests (ADF and KPSS) to define the geographic relevant market. The results of these tests indicated an international geographic relevant market which was corroborated analysing the functioning of this market. After these tests, a market power test was done, because in this market, the world leader is a brazilian company, Aracruz. This test was proposed by Mayo, Kaserman e Kahai (1996) and they used a demand residual model. The estimation of this test was proposed by Motta (2004). The results indicated that Aracruz does not have market power in this sector.